SAT0254 VASODILATOR THERAPY IN THE LONG TERM PREVENTION OF MYOCARDIAL MANIFESTATIONS IN SYSTEMIC SCLEROSIS (SSC): RESULTS FROM DESSCIPHER INCEPTION COHORT STUDY. (June 2019) - Riccardi, Antonella; Husher, Dorte; Fasano, Serena; Messiniti, Valentina; Allanore, Yannick; Avouac, Jérôme; Czirják, László; Lorand, Veronika; Galdo, Francesco Del; Abignano, Giuseppina; Denton, Christopher; Nihtyanova, Svetlana; et al.
Abstract : Background: Calcium channel blockers (CCB) and angiotensin converting enzyme inhibitors (ACEinh) are known to improve in the short term, cardiac perfusion and function in patients with SSc (Parks JL et al. Rheum Dis Clin North Am 2014). No study has been carried out so far to investigate the long-term effectiveness of these drugs. Objectives: To address this topic and other aspects of the management of SSc, the DeSScipher (To decipher the optimal treatment of SSc) project was submitted to and financed by the European Community (FP7- HEALTH n°305495). Methods: From Dec.1, 2012 to Nov. 30, 2015, 512 SSc patients who, as inclusion criterion, had no significant gut or lung or kidney involvement, were treated for 0.5-4 years (median 2.31) with either (n= 359: group 1) vasodilator treatment (i.e. CCB, or ACE-inh or Angiotensin II receptor blockers [AgIIrb] or a combination of them i.e. CCB plus either ACEinh or AgIIrb) or (n= 153:group 2) no vasodilator therapy. The 296 patients of the 2 groups, who had been assessed at baseline and along the follow-up for conduction blocks (CB), ventricular arrhythmias (VA), pacemaker implantation (PMI), left ventricular ejection fraction (LVEF) < 55%) and congestive heart failure (CHF), and sudden cardiac death (SCD) during follow-up, were investigated for the cumulative incidence rate (IR) of all these events. The IR of single manifestations were calculated in the patients investigated for each of them. Cox regression analysis was carried out in the 296 patients with no missing value to identify independent predictors of the occurrence of any myocardial manifestation. Results: During 1164 patient-years follow-up, 6/508 were implanted a PM, 10/506 developed a LVEF<55%, 2/492 a CHF, 11/325 a VA, 36/305 a CB, none underwent a SCD, any of these manifestations intervening in 59 out of the 296 investigated for all the manifestations. The IR of PMI and VA was greater in group 2 patients as compared with group 1 (1.3 vs 0.2x100 pts/year; p=0.02) and (2.7 vs 1.1x100 pts/year; p=0.077). In stepwise Cox regression analysis, male gender (HR 2.44, 95%CI 1.3-4.6; p=0.005), age at enrollment (HR 2.97, 95%CI 1.7-5.2; p=0.0002) and vasodilator therapy (HR 0.41, 95%CI 0.2-0.7; p=0.002) were independent positive and respectively, negative predictors of new onset cardiac manifestations. Conclusion: Long term vasodilator therapy is likely to have a preventative role on the occurrence of myocardial manifestations of SSc. Disclosure of Interests: Antonella Riccardi: None declared, Dorte Husher: None declared, SERENA FASANO: None declared, Valentina Messiniti: None declared, Yannick Allanore Grant/research support from: Inventiva, F Hoffman La-Roche, Sanofi, BMS, Pfizer, Consultant for: Actelion, Bayer, BMS, Boehringer, Roche, Sanofi, Jérôme Avouac Grant/research support from: research grant from Pfizer, László Czirják: None declared, Veronika Lorand: None declared, Francesco Del Galdo: None declared, Giuseppina Abignano: None declared, Christopher Denton Grant/research support from: GlaxoSmithKline, Inventiva, CSF Behring, Consultant for: Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Bayer, Svetlana Nihtyanova: None declared, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders, Britta Maurer Grant/research support from: Grant/research support from AbbVie, Protagen, Novartis; congress support from MSD, Pfizer, Roche, and Actelion, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen, Serena Guiducci: None declared, Gabriela Riemekasten Consultant for: Chugai, F. Hoffmann-La Roche, Speakers bureau: Chugai, F. Hoffmann-La Roche, Elise Siegert Shareholder of: Astra Zeneca, Grant/research support from: Actelion, Consultant for: AEC Partners, Speakers bureau: Actelion, Norsk, Ulrich Walker Grant/research support from: Unrestricted grant from AbbVie for the creation of the COmPASS II app, Veronika Jaeger Grant/research support from: Has received an unrestricted grant from AbbVie to support the creation of the COmPASS II app, Marc Frerix: None declared, Ingo Helmut Tarner: None declared, Ulf Müller-Ladner Grant/research support from: Projekt supported by an unrestricted educational grant from Celgene GmbH., Gabriele Valentini Grant/research support from: MSD, Phizer, Consultant for: MSD, Phizer, biogen, Speakers bureau: MSD, amgen, biogen, lilly, sanofi, phizer